Diabetes and hypercholesterolemia among a tribal population in Tamilnadu, India - T., Nikkin; Stanly, Meriton (International Journal Of Community Medicine And Public Health, 2017)
Background: It is predicted that diabetes will become the 7th leading cause of death in the world by the year 2030. The global prevalence of diabetes in 2014 was estimated to be 9% in adults aged 18+ years. Raised total cholesterol is a major cause of disease burden in both the developed and developing world as a risk factor for ischemic heart disease and stroke. The present study was done to determine the blood glucose and cholesterol levels among a tribal population in Tamil Nadu. The objective of the study was to estimate the proportion of population having diabetes and hypercholesterolemia attending primary health centre in a tribal area. Methods:The present study was carried out among tribal population in Athanavoor Primary Health Centre in Yelagiri hill station of Vellore District, Tamilnadu. The study was done for a period of two weeks from 25th December, 2014 to 08th January, 2015. Individuals aged 25 to 65 years were selected for the study. Blood samples were collected to estimate Fasting Blood Sugar and Serum Cholesterol levels. The data entry and statistical analysis were done by SPSS software version 16.0 Results: Out of 104 participants, 29(27.9%) are males and 75(72.1%) are females. The proportion of participants who had diabetes mellitus is 3.8% with a 95% confidence interval of 1.1% to 9.6%.About 6% of the participants had borderline hypercholesterolemia with a 95% confidence interval of 2.1% to 12.1%. The difference in mean total cholesterol levels of men and women is statistically significant with a p value of 0.009. Conclusions:The proportion of participants with impaired fasting glucose levels and borderline hypercholesterolemia from this study suggests that these risk factors should be taken care of in Tribal population at the earliest to prevent these people from developing CHD in the later years.